Gender Eclipsed? Racial Hierarchies in Transnational Call Center Work - Mirchandani, Kiran (Social justice, 2005)
Part of a special issue on race, racism, and empire in the Canadian context. A study was conducted to explore the nature of gendered work in the context of global economic relations. Data were obtained from interviews with 13 workers, three managers, and representatives of three agencies that provide training for workers in the call center industry in New Delhi, India. Findings revealed that the participants considered call center work to be gender-desegregated. However, findings further revealed that female workers visualized their call center work as an opportunity to gain entry into technical work, whereas male workers construct call center jobs as fundamentally non-technical. Findings suggest that traditionally female-dominated service industries are being redefined as technical and exported to countries with a low-cost labor pool to be staffed by well-educated workers of both sexes.